Dewan Perwakilan Rakyat Daerah (DPRD) Dalam Perundang-Undangan Pemerintahan Daerah dan Lembaga Legislatif Daerah - Asmawi . (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Local People's Representative Council (DPRD) In Local Government Legislation and Regional Legislative Institutions. One of the most esential issues of democracy’s results in Indonesian constitutional platform is the local legislature, so popularly known as the Local People's Representative Council (DPRD). The key of the success in organizing local government is the capability of the Local People's Representative Council (DPRD) in conducting the three basic functions and plus, namely legislating, budgeting, supervising, and plus representing, simultaneously, proportionally and continously. In the future times, it is urgent to strengthen the structure and institutional capacity of the Local People's Representative Council (DPRD) by means of three agenda, that is (i) to redefine and to consolidate the position of the Local People's Representative Council (DPRD) as a legislature; (ii) to reinforce the authority of the Local People's Representative Council (DPRD); and (iii) to maximize the capacity of the Local People's Representative Council (DPRD) in performing its all functions. To that end, it is urgent to take an effort in revising Law of 32/2004 and Law of 27/2009. Abstrak: Dewan Perwakilan Rakyat Daerah (DPRD) Dalam Perundangundangan Pemerintahan Daerah dan Lembaga Legislatif Daerah. Salah satu isu terpenting hasil demokrasi dalam pentas ketatanegaraan Indonesia ialah lembaga legislatif daerah, yang populer dikenal dengan Dewan Perwakilan Rakyat Daerah (DPRD). Kunci keberhasilan penyelenggaraan pemerintahan daerah adalah kemampuan DPRD dalam menjalankan tiga plus fungsi utamanya-legislasi, anggaran dan pengawasan, dan plus representasi‐secara simultan, proporsional dan berkelanjutan. Di masa mendatang penting untuk memperkuat struktur dan kelembagaan DPRD melalui 3 (tiga) agenda: (i) memperjelas dan memperkuat kedudukan DPRD sebagai badan legislatif; (ii) memperkuat kewenangan DPRD; dan (iii) memperkuat kapasitas DPRD dalam menjalankan fungsi-fungsinya. Untuk itu, diperlukan segera upaya merevisi UU 32/2004 dan UU 27/2009 DOI: 10.15408/jch.v1i1.1443